Genetic analysis of the equine orthologues for human CYP2D6: unraveling the complexity of the CYP2D family in horses - Scantamburlo, Giada; Nofziger, Charity; Paulmichl, Markus; Vanoni, Simone (Frontiers in Veterinary Science, 2023)
Introduction Because of their importance as companion animals or as racehorses, horses can be treated with various drugs. Although it is known that drug withdrawal times can vary for each horse, pharmacogenetics for these animals has not been adequately studied and requires further development. Since CYP2D6 is responsible for the metabolism of 25-30% of drugs in humans, including some used to treat horses, a study of the CYP2D family in horses was conducted to define its genetic structure as well as its expression pattern in the liver. Methods Genomic DNA extracted from venous blood and mRNA from fresh liver tissue were amplified and sequenced to analyze the genomic structure, genotype, and expression of the various enzymes that are part of the equine orthologous family for CYP2D6. Results Amplification and sequencing of the gDNA of CYP2D50, the major CYP2D6 orthologue identified in previous studies, revealed a novel putative genomic structure for this gene compared with that reported from the EquCab3.0 assembly, including the formation of a hybrid structure similar to what happens in human CYP2D6. At the mRNA level, transcripts from six different members of the equine CYP2D family were detected in horse liver. In addition, genotyping of CYP2D50 and CYP2D82 revealed the presence of several polymorphisms, six of which result in novel, nonsynonymous amino acid changes for each of the two genes. Discussion This study aimed to elucidate the pharmacogenetic analysis of the CYP2D family in horses and resulted in the identification of a novel gene structure for CYP2D50, the expression of six different members of the CYP2D family in horse liver, and several novel polymorphisms for CYP2D50 and CYP2D82.